2021
DOI: 10.1002/aesr.202100055
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Improvement of Bimetallic Electronegativity on Metal–Organic Frameworks for Electrocatalytic Water Oxidation

Abstract: Development of efficient energy conversion and storage devices such as electrolyzers, regenerative fuel cells, and rechargeable fuel cells is vital to solve the deteriorating environmental issue caused by the consumption of fossil fuels. [1][2][3] However, the overall performance of these devices are still hindered, due to the sluggish kinetics of oxygen evolution reaction (OER) which is a complex four-electron transfer reaction. [4][5][6][7] To promote OER in the electrocatalytic overall water splitting, elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…, number of low coordination sites generated in the nanostructure) should be considered when designing active and stable OER electrocatalysts. Various approaches have not yet overcome the limitations in the volcano relationships. …”
Section: Introductionmentioning
confidence: 99%
“…, number of low coordination sites generated in the nanostructure) should be considered when designing active and stable OER electrocatalysts. Various approaches have not yet overcome the limitations in the volcano relationships. …”
Section: Introductionmentioning
confidence: 99%
“…Currently, the research on a non-noble-metal electrocatalyst has made great progress; transition metal nitrides (TMNs) are regarded as one of the appropriate OER electrocatalysts, due to the fact that the introduction of N atoms can change the d-band electron state density of the transition metal and accelerates the electron transfer, such as Fe x N, Co 4 N, and Ni 3 N. , Recently, bimetallic nitrides have attracted widespread attention, because the introduction of additional metal atoms can provide a synergistic effect that obviously enhances the OER electrocatalytic activity. Ni 3 Mo 3 N is formed by the insertion of N atoms into Ni–Mo bonds, and due to this unique structure, it has great research value in catalysis, , such as water splitting, CO 2 (dry) methane reforming reaction (DRM), and ammonia decomposition reaction . Su and co-workers reported that Ni 3 Mo 3 N was synthesized by calcining the dried and calcined NiMoO 4 precursor in three stages and passivated by 0.1% O 2 /N 2 , but the products contained impurity Ni 0.2 Mo 0.8 N .…”
Section: Introductionmentioning
confidence: 99%
“…The Nyquist plots for all catalysts and the equivalent circuit were displayed in Figure and Figure S7 of the Supporting Information. The R s , R ct /CPE ct , and CPE ads referred to the solution resistance, carrier transfer component in series, and constant phase elements to solve the unevenness of the catalyst surface . The detailed fitting constants were listed in Table S2 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The R s , R ct /CPE ct , and CPE ads referred to the solution resistance, carrier transfer component in series, and constant phase elements to solve the unevenness of the catalyst surface. 55 The detailed fitting constants were listed in Table S2 of…”
Section: Interfacial Band Alignmentmentioning
confidence: 99%